Wintergreen Oil: A Boon or Curse - S Deepak; N S Harsha; B M Suraj; Supreeth S Kanakavidu; G G Mayuka; R Monisha (Wolters Kluwer Medknow Publications, 2022)
"All things are poison and nothing is without poison, only the dose permits something not be poisonous" - Paracelsus. Some substances are so toxic that small amounts can be harmful. Here is a case detail about a 58-year-old male who consumed a small quantity of methyl salicylate, mistaking it to Indian blackberry juice. He ended up undergoing six cycles of hemodialysis and critical care polyneuropathy.